Integrative genomic analysis identifies DPP4 inhibition as a modulator of FGF17 and PDGFRA downregulation and PI3K/Akt pathway suppression leading to apoptosis - Chitluri, Kiran Kumar; Arnold, Emerson Isaac (Frontiers in Pharmacology, 2025)
IntroductionProstate cancer (PCa) remains a significant global health challenge despite advancements in treatment strategies. There is a need to explore the molecular heterogeneity of PCa to facilitate the development of personalized treatment approaches. This study investigates the molecular heterogeneity of PCa by combining genomic and transcriptomic data using a systems biology approach.MethodsBy utilising whole-genome sequencing and differentially expressed genes from “The Cancer Genome Atlas Prostate Adenocarcinoma (TCGA-PRAD)” patient samples, we identified 357 intersecting genes. From protein-protein interaction network analysis, 22 hub genes were identified as critical regulators associated with PCa prognosis and pathogenesis. Furthermore, these hub genes were subjected to functional and pathway enrichment analysis via gene ontology (GO) and the Kyoto Encyclopaedia of Genes and Genomes (KEGG).ResultsNotably, the PI3K/Akt signalling pathway was significantly enriched with eight of these hub genes, with significant clinical relevance. Dipeptidyl Peptidase 4 (DPP4) emerged as a promising therapeutic target. Further, in vitro assays were performed to investigate and validate the molecular role of DPP4 through pharmacological inhibition using Linagliptin, a selective DPP4 inhibitor. Inhibition of DPP4 led to the induction of apoptosis, G1/S phase cell cycle arrest, and significant suppression of cell proliferation and migration in PC3 and DU145 cell lines.DiscussionThese experiments revealed novel downstream regulatory effects of DPP4, demonstrating that its inhibition results in the transcriptional downregulation of FGF17, PDGFRA, COL4A1, and COL9A2, thereby contributing to the inactivation of the PI3K/Akt signaling pathway. Collectively, these findings highlight DPP4 as a potential therapeutic target for the treatment of PCa.